2006
DOI: 10.3200/genp.133.1.19-35
|View full text |Cite
|
Sign up to set email alerts
|

Hot or Not: Do Professors Perceived as Physically Attractive Receive Higher Student Evaluations?

Abstract: Previous research investigating the influence of perceived physical attractiveness on student evaluations of college professors has been limited to a handful of studies. In this study, the authors used naturally occurring data obtained from the publicly available Web site www.ratemyprofessors.com. The data suggested that professors perceived as attractive received higher student evaluations when compared with those of a nonattractive control group (matched for department and gender). Results were consistent ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(90 citation statements)
references
References 39 publications
8
76
0
6
Order By: Relevance
“…A review of the literature provides three possible explanations: (a) previous studies have not always attended to possible differences between perceptions of same-sex versus other-sex targets (e.g., Nicklin & Roch, 2008;Riniolo, Johnson, Sherman, & Misso, 2006), (b) some previous studies have used targets (e.g., children) who are unlikely to elicit perceptions of competition or threat in the participant (Langlois, Ritter, Casey, & Sawin, 1995), and (c) many studies have only compared relatively attractive to relatively less attractive targets and have not examined responses to targets who are particularly high in attractiveness (e.g., Jawahar & Mattsson, 2005)-targets for whom negative responses by same-sex persons should be most pronounced. One further explanation is suggested by the current findings: In each study, the positive bias toward attractive other-sex targets was relatively larger in magnitude than the negative bias against attractive same-sex targets.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature provides three possible explanations: (a) previous studies have not always attended to possible differences between perceptions of same-sex versus other-sex targets (e.g., Nicklin & Roch, 2008;Riniolo, Johnson, Sherman, & Misso, 2006), (b) some previous studies have used targets (e.g., children) who are unlikely to elicit perceptions of competition or threat in the participant (Langlois, Ritter, Casey, & Sawin, 1995), and (c) many studies have only compared relatively attractive to relatively less attractive targets and have not examined responses to targets who are particularly high in attractiveness (e.g., Jawahar & Mattsson, 2005)-targets for whom negative responses by same-sex persons should be most pronounced. One further explanation is suggested by the current findings: In each study, the positive bias toward attractive other-sex targets was relatively larger in magnitude than the negative bias against attractive same-sex targets.…”
Section: Discussionmentioning
confidence: 99%
“…Female teachers were rated more attractive than male teachers; as well as, the ones who explain the lesson more clearly (2007). Other data along a similar vein (available on www.ratemyprofessors.com), point out that professors received high evaluations from their students once acknowledged as physically attractive by these students (Riniolo et al, 2006). And yet, although Raacke and Raacke reported a significant correlation between instructors' attractiveness and how highly they are evaluated by students, the instructors' clarity and efficiency in delivering the subject matter, helpfulness in un-clearing assignments and stimulation in problem solving remain highly valued by the students.…”
Section: Gender Dynamics In the Classroommentioning
confidence: 99%
“…In contrast, Riniolo et al (2006), who also analysed data provided by the website RateMyProfessors.com, suggested that professors perceived as attractive receive better student evaluations regardless of their gender. Hamermesh/Parker (2005), who analysed data collected at the University of Texas at Austin, came to the conclusion that the influence of perceived attractiveness on students' instructional ratings is larger for male than for female…”
Section: Introductionmentioning
confidence: 99%